Islamic Republic of Iran : Report on the Observance of Standards and Codes-Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This report assesses the Observance of Standards and Codes on Fiscal Transparency for the Islamic Republic of Iran. Since the enactment of the five-year Development Plan covering 2000-04, the authorities have taken a number of steps to enhance fiscal transparency, especially with respect to the budget process. Important recent actions include eliminating implicit exchange rate subsidies, budgetizing other implicit subsidies including those associated with price controls, and adopting contemporary budget classification standards. The audit framework for the public sector has a robust legal framework and follows international auditing standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet